Can and “should” Qualitative Research Be ValueFree? Understanding the Epistemological Tussle between Positivists and Interpretivists1 - Dr. Dayyab Gillani (Journal of Political Studies, 2021)
This paper seeks to address the question of value-free research in qualitative methods. The primary argument of the paper is that qualitative research is not value-free because it is not intended to be as such. It analyzes this question by tracing the roots of qualitative research at the ontological and epistemological level. It argues that qualitative research tradition has evolved out of constructivism and interpretivism both of which prioritize people’s interpretation and discount objectivity in social science research. Furthermore, the paper argues that social science research cannot be value-free because of strong ethical considerations. All the cases presented in the paper will fundamentally try to show that all qualitative research is essentially subjective not just because of the impediments but because it is not designed to be value-free.